Analisis Pengaruh Inflasi , Bank Indonesia Rate , Nilai Tukar Rupiah Terhadap Nilai Aktiva Bersih Danareksa Syariah Berimbang : Periode Januari 2012 - Desember 2014 - Citraningtiyas, Pipit; , Siti Fatimah, SE, M.Si; , Nurul Huda, S.Ag, M.Ag (2006)
This study entitled "analysis of the effects of inflation, Bank Indonesia rate, kurs the net asset value (NAV) of sharia mutual funds (danareksa syariah berimbang) impartial period January 2012 to December 2014. The goal is to analyze the effect of inflation, Bank Indonesia rate, kurs the net asset value (NAV) of sharia mutual funds (danareksa syariah berimbang) impartial period January 2012 to December 2014. The dependent variable is net asset value (NAV) of sharia mutual funds (danareksa syariah berimbang), while the independent variable is inflation, Bank Indonesia rate, kurs. This study uses secondary date using analytical methods Partial Adjustment Model (PAM). Validity test results can beseen that the influence of the variables that negatively and significant the NAV is inflasion and BI rate (in the short-term and long term) and variable positive and significant effect is the kurs and net asset value of the previous year (in the short-term).